Analisis Penggunaan Media Sosial dan Penyebaran Hoax Di Kota Medan - Munzaimah Masril; Fatma Wardy Lubis (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
The growing of Hoaxes through social media at this time has recognized due to the lack of awareness from social media users in the selection process for diffuse information. Ignoring the validation process of the information often happens because the nature of social media is a medium that is still private with the use of passwords, so that with the increasing number of people using social media such as Facebook, Instagram, and Twitter. This is a qualitative research that using interviews and Focuss Group Discussions (FGD) as a method for collecting data. The results of this study explain how the Hoax phenomenon in Medan and show the importance of collaboration between stakeholders to resolving the Hoax phenomenon.